Neuroprotective Effect of Crocin on Rats with Focal Cerebral Ischemia-Reperfusion Injury Based on TLR4/NF-κB Pathway - LI Xiaolei; ZHU Haisheng; MA Ruijuan; HU Ke; FENG Lina; WANG Xudong (康复学报)
ObjectiveTo observe the protective effect of crocin on neurons of rats with focal cerebral ischemia-reperfusion (FCIR) injury based on the toll-like receptor 4 (TLR4)/nuclear factor-κB (NF-κB) pathway, and to explore the possible mechanism of crocin in the prevention and treatment on FCIR injury.MethodsA total of 128 SD rats were divided randomly into sham operation group, model group, crocin group, crocin + lipopolysaccharide group, with 32 rats in each group. From seven days before modeling, the crocin group was intraperitoneally injected with crocin solution; the crocin + lipopolysaccharide group was intraperitoneally injected with crocin solution and lipopolysaccharide solution; the sham operation group and the model group were intraperitoneally injected with normal saline. All groups were injected 5 mL/(kg·d), once a day, lasting for seven days. Suture occluded method was used to establish FCIR rats model. After reperfution for 24 h, modified neurological severity score (mNSS) was used to evaluate the neurological deficits; triphenyltetrazolium chloride (TTC) staining method was used to evaluate cerebral infarction rate, and dry-wet method was used to evaluate brain water content; hematoxylin-eosin staining (HE) staining and TUNEL staining were used to observe pathological changes and apoptosis of cortical neurons; ELISA method was used to detect the level of inflammatory factors in brain tissue (TNF-α, IL-1β, IL-6, etc.); western blot was used to detect the expression of toll-like receptor 4 (TLR4), nuclear factor-κB p65 (NF-κB p65), p-NF-κB p65, IκBα, p-IκBα, Cleved Caspase-3, B-lymphoma-2 gene (Bcl-2), Bcl-2-related X protein (Bax).Results(1) Neurological function, cerebral infarction rate and cerebral water content: compared with the sham operation group, the mNSS score, cerebral infarction rate, cerebral water content in the model group increased significantly (P<0.05); compared with the model group, the mNSS score, cerebral infarction rate, cerebral water content in the crocin group and the crocin + lipopolysaccharide group decreased significantly (P<0.05); compared with the crocin group, the mNSS score, cerebral infarction rate, cerebral water content in the crocin + lipopolysaccharide group increased significantly (P<0.05). (2) Pathological changes and apoptosis of cortical neurons: the cortical neurons in the sham operation group showed normal morphology and complete structure; the pathological changes of cortical neurons such as disordered arrangement, decreased number, vacuolar degeneration, hyperchromatic cytoplasmic pyknosis, unclear nuclear membrane boundary, inflammatory cell infiltration were observed in the model group; the pathological changes of cortical neurons in the crocin group were significantly improved. Compared with the sham operation group, the apoptosis index of cortical neurons in the model group increased significantly (P<0.05); compared with the model group, the apoptosis index of cortical neurons in the crocin groupand the crocin + lipopolysaccharide group decreased significantly (P<0.05); compared with the crocin group, the apoptosis index of cortical neurons in the crocin + lipopolysaccharide group increased significantly (P<0.05).(3) Inflammatory factor level: compared with the sham operation group, the level of TNF-α, IL-1β, IL-6 in the model group increased significantly (P<0.05); compared with the model group, the level of TNF-α, IL-1β, IL-6 in the crocin group and the crocin + lipopolysaccharide group decreased significantly (P<0.05);compared with the crocin group, the level of TNF-α, IL-1β, IL-6 in the crocin + lipopolysaccharide group increased significantly (P<0.05). (4) Expression of proteins: compared with the sham operation group, the expression of TLR4, Cleved Caspase-3 and the ratio of p-NF-κB p65/NF-κB p65, p-IκBα/IκBα, Bax/Bcl-2 in the model group increased significantly (P<0.05); compared with the model group, the expression of TLR4, Cleved Caspase-3 and the ratios of p-NF-κB p65/NF-κB p65, p-IκBα/IκBα, Bax/Bcl-2 in the crocin group and the crocin + lipopolysaccharide group decreased significantly (P<0.05); compared with the crocin group, the expression of TLR4, Cleved Caspase-3 and the ratios of p-NF-κB p65/NF-κB p65, p-IκBα/IκBα, Bax/Bcl-2 in the crocin + lipopolysaccharide group increased significantly (P<0.05).ConclusionCrocin can inhibit the inflammatory reaction and cortical neurons apoptosis in FCIR rats, and reduce the damage of cortical neurons. The mechanism may be related to the inhibition of TLR4/NF-κB pathway activation.